Fabrication of polymer nanocavities with tailored openings - Tan, Li Huey (2012)
A templated fabrication of open nanocavities is reported, where rational control of partial polymer attachment on sacrificial metal cores introduces openings in the polymer shells. This approach provides a facile means to modify the structural features of polymer nanocavities by manipulating the surface chemistry of colloidal nanoparticles. In particular, the anisotropic geometry of gold nanorods is exploited to promote the anisotropic polymer attachment, such that two diametric openings occurred in the polymer shell. After etching the gold nanorods, this approach yields open nanochannels that are tunable in both diameter and length. The synthetic scope of the anisotropic core/shell nanoparticles is expanded, supporting the previously proposed mechanism. We demonstrate that reducing the symmetry of nano-objects could open up new ways to create structural features using simple assembly and etching techniques. The thermostability of the open polymer nanostructures is also investigated.